A gold(i)-catalysed three-component reaction via trapping oxonium ylides with allenamides. Issue 84 (7th October 2019) - Liu, Gengxin; Yu, Sifan; Hu, Wenhao; Qiu, Huang
Abstract : A gold(i )-catalysed three-component reaction between alcohols (and water), α-aryl-α-diazoesters and allenamides is reported, affording tert -allylic ethers (and alcohols), in moderate to excellent yields with excellent geometric selectivity. Abstract : A gold(i )-catalysed three-component reaction between alcohols (and water), α-aryl-α-diazoesters and allenamides has been developed, affording three-component products, tert -allylic ethers (and alcohols), in moderate to excellent yields with excellent geometric selectivity ( E  :  Z > 20 : 1). In addition, this transformation proceeds smoothly with high functional group tolerance and a broad substrate scope under exceptionally mild reaction conditions. Remarkably, a gram-scale reaction is also successfully performed, and the corresponding three-component product can readily react with easily obtained reagents, furnishing diverse products in satisfactory yields.